Vitality of the Aymara Language - Huayhua Pari, Felipe (2013)
Vitality in the Aimara language can be assessed in several ways and you can be seen it as an endangered language. In this appraisal there are some factors arising from a ground of positive cultural diversity may influence the process of asserting a groups’s own identity or, to understand respect the identity of the others.In this last point the political (ie, attaining official status), religious, scholarly (chair of Aimara), literary (written sources), territorial, identity and ethnic resistance aspects can be seen as factors of vitality. But identity and self-esteem can also be reflected in the number of speakers, by social prestige, availability of media, and its use historical and cultural codification, and ways of expressing each other the words and by oneself.